On the Interaction between Minimum Wage Adoption and Fiscal Redistribution: A Theoretical and Empirical Investigation - George Economides; Pantelis Kammas; Thomas Moutos (Center for Economic Studies and Ifo Institute (CESifo), 2020)
We explain the public's support for the minimum wage (MW) institution despite economists' warnings that the MW is a “blunt instrument” for redistribution. To do so we build a model in which workers are heterogeneous in ability, and the government engages in redistribution through the public provision of private goods. We show that the MW institution is politically viable only when there is a limited degree of in-kind redistribution. To examine the empirical relevance of our hypothesis we investigate the relationship between the probability of adopting MW legislation and the size of primary government spending by employing a dataset of 38 -developing and developed- countries from 1960 to 2017. Probit model estimations yield support for our theoretical prediction that a decrease in government spending increases the likelihood of a country enacting MW legislation. This negative association remains highly robust under alternative empirical specifications and estimation techniques.
Keywords: E21; E24; H23; J23; 330; minimum wage; redistribution; heterogeneity; unemployment